LACK OF MOTHER’S PERSONAL HYGIENE RELATED TO DIARRHEA INCIDENT TO THE CHILDREN UNDER FIVE YEARS OLD IN PEDIATRIC WARD - Wahyu Setiani, Devita Maharani; Yusiana, Maria Anita (Jurnal Penelitian STIKES Kediri, 2013)
One of the factors that cause diarrhea in children under five years old is contaminated food and generally it is because the poor personal hygiene in food processing performed by caregivers of child under five years old, especially mother. The purpose of this study to analyze the corelation between individual hygiene patern and the frequency of diarrhea incident to children under five years old in pediatric ward of Kediri Baptist Hospital. The design of this study was correlation analytic. The respondents in this study were mothers who had child under five years old who had suffered from diarrhea. The numbers of sample were 34 respondents with purposive sampling method. The independent variable was personal hygiene pattern and the dependent variable was frequency of diarrhea incident. The data was collected by quetionare and then analized using Spearman’s Rho with significance level α < 0, 05 and diarrhea incidents frequencies by interviewing the mother. The results showed p = 0.000 with a correlation coefficient of -0.882, The conclusion is poor personal hygiene of mother will increase the incidence of diarrhea in children under five years old.